Detection of a New Resistance-Mediating Plasmid Chimera in a bla(OXA-48)-Positive Klebsiella pneumoniae Strain at a German University Hospital - HASDEMİR GÖKBOĞA, MÜNEVVER UFUK (MDPI, 2021)
Mobile genetic elements, such as plasmids, facilitate the spread of antibiotic resistance genes in Enterobacterales. In line with this, we investigated the plasmid-resistome of seven bla(OXA-48) gene-carrying Klebsiella pneumoniae isolates, which were isolated between 2013 and 2014 at the University Medical Center in Gottingen, Germany. All isolates were subjected to complete genome sequencing including the reconstruction of entire plasmid sequences. In addition, phenotypic resistance testing was conducted. The seven isolates comprised both disease-associated isolates and colonizers isolated from five patients. They fell into two clusters of three sequence type (ST)101 and two ST11 isolates, respectively; and ST15 and ST23 singletons. The seven isolates harbored various plasmids of the incompatibility (Inc) groups IncF, IncL/M, IncN, IncR, and a novel plasmid chimera. All bla(OXA-48) genes were encoded on the IncL/M plasmids. Of note, distinct phenotypical resistance patterns associated with different sets of resistance genes encoded by IncL/M and IncR plasmids were observed among isolates of the ST101 cluster in spite of high phylogenetic relatedness of the bacterial chromosomes, suggesting nosocomial transmission. This highlights the importance of plasmid uptake and plasmid recombination events for the fast generation of resistance variability after clonal transmission. In conclusion, this study contributes a piece in the puzzle of molecular epidemiology of resistance gene-carrying plasmids in K. pneumoniae in Germany.
Keywords: Klebsiella pneumoniae; carbapenem resistance; beta-lactamase; resistome; plasmid; phylogeny; epidemiology